THE INFLUENCE OF POPULATION DYNAMICS OF THE REPUBLIC OF ARMENIA ON THE BALANCED TERRITORIAL DEVELOPMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
One of the priority tasks of the socio-economic develeopment of the Republic of Armenia is its balanced territorial development. The solution to this strategic problem also depends on the identification of existing trends and changes in the placement and redistribution of the RA population. The article presents the territorial differences in the distribution of the population, caused by its dynamics, which took place over the past three decades, and the resulting aggravation of the problems of balanced territorial development, and indicates the ways of their solution.
Keywords: RA population distribution and redistribution; population dynamics; balanced territorial development; problems